Indigenous Child and Doctor at Las Islas Clinic - Bacon, David
OXNARD, CA - At the Las Islas Clinic in Oxnard pregnant women and mothers and children from Oaxaca and Guerrero receive health care in their native Mixtec language. Pictured: Family Nurse Practitioner Sandy Young and Maria Tiburcio